القواعد الأصولية وطرق استنباط الأحكام منها - مصطفى، محمد شريف (الجامعة الإسلامية بغزة - عمادة البحث العلمي والدراسات العليا, 2011)
يتناول هذا البحث القاعدة الأصولية بمعناها الخاص لها، والتـي يعتمـد عليهـا المجتهد في استخراج الأحكام الشرعية المتعلقة بأعمال المكلفين كالعبادات والمعاملات، أو الترجيح بين الأقوال الفقهية المختلفة المتنافية. وقد تناول هذا البحـث تعريـف القاعـدة الأصولية، وأهميتها التشريعية، وسماتها، والمستندات التي تقوم عليها، وأقسامها، وطـرق استنباط الأحكام الشرعية منها. This paper deals with fundamentals of methodology (Qawaid al- usol) in the particular meaning thereof, on with the jurisprudent rely in deriving jurisprudential verdicts relating to the responsible actions such as, worships and transactions, or weighting between the different incompatible juris prudential state mints Also, this paper deals with the definition of a fan demented of methodology, its jurisprudential importance, characteristics and divisions. Furthermore, it deals with references on which fundamentals of methodology rely on and methods for deriving juris prudential verdicts therefrom.
740314
Keywords: الشريعة الإسلامية -- القواعد الأصولية -- علم أصول الفقه -- الفقه الإسلامى